Відкриття одерону колабораціями D0 і TOTEM - Royon, Ch.; on behalf of the D0 and TOTEM Collaborations (Publishing house "Academperiodika", 2024)
After a brief introduction of the odderon, we will describe its experimental discovery by the D0 and TOTEM collaborations by comparing pp and pp- elastic scattering data and by combining it with the ρ and total cross section measurements by the TOTEM collaboration.